KNOWING THE RISKS BUT CONTINUING ANYWAY? EXPLAINING SUSTAINED BUY NOW, PAY LATER USAGE AMONG GENERATION Y AND Z - Wan Nawang, Wan Rasyidah; Jasazami, Syakirah; Anwar, Intan Fatimah; Nordin, Siti Nurulhuda (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Buy Now, Pay Later (BNPL) services have significantly reshaped payment behaviour among digitally engaged Generation Y and Generation Z consumers. Despite their rapid adoption, limited research has examined the behavioural, technological, and financial factors influencing consumers’ continuance intention to use BNPL services. This study investigates the influence of perceived ease of use, perceived usefulness, social influence, financial literacy, attitude, and trust on continuance intention to use BNPL services, with attitude and trust examined as mediating variables. This quantitative study used a structured online survey distributed to respondents chosen via convenience sampling. A total of 219 valid responses were received from the Generation Y and Generation Z respondents. The data were then analysed using Partial Least Square Structural Equation Modelling (PLS-SEM) to determine the direct and indirect relationships. Perceived ease of use and perceived usefulness were found to significantly improve trust, which subsequently drives continuance intention. Financial literacy and social influence also showed a significant effect in strengthening attitudes toward BNPL services, which in turn significantly influence continuance intention. Trust and attitude were also found to significantly mediate the relationships between the antecedent variables and continuance intention. Based on the findings, continuance intention toward BNPL services is driven by both cognitive and relational factors, indicating the need to improve users’ financial capability, technological perceptions, positive attitudes, and trust to maintain their engagement over the long run.